2021
DOI: 10.3390/ijerph18030921
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Land Use Pattern Evolution from a Multi-Scenario Perspective: A Case Study of Suzhou City in Anhui Province, China

Abstract: Land use/land cover change is a frontier issue in the field of geography research. Taking Suzhou City in Anhui Province as the research case, based on thematic mapper /enhanced thematic mapper+ (TM/ETM+) remote sensing data from 1998 to 2018, through the transfer matrix model and modified conversion of land use and its effects at small region extent (CLUE-S) model, the simulation of the land use landscape pattern evolution was studied from a multi-scenario perspective. The results showed that in the past 20 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The Markov transfer matrix was initially applied to describe of the state and state transition over a certain period and gradually extended to the field of land management, known as the land-use transfer matrix (LUTM) [56]. It has been widely employed in mass literatures to gain in-depth insight of the evolution process of land-use change [58,59]. It is helpful to comprehensively explain the mutual conversions among different land-use types [60,61].…”
Section: Land-use Transfer Matrixmentioning
confidence: 99%
“…The Markov transfer matrix was initially applied to describe of the state and state transition over a certain period and gradually extended to the field of land management, known as the land-use transfer matrix (LUTM) [56]. It has been widely employed in mass literatures to gain in-depth insight of the evolution process of land-use change [58,59]. It is helpful to comprehensively explain the mutual conversions among different land-use types [60,61].…”
Section: Land-use Transfer Matrixmentioning
confidence: 99%
“…Baokang is a famous mountainous county with more than 3100 hilltops, so it is more suitable for forestry and fruit farming since the singular topography promotes the development of NGP. The central and eastern parts of Hubei Province are abundant in rainfall and heat, which help the growth of crops [72]. Jianghan Plain, which has a large number of agricultural exports, has fertile soil and an extensive water network.…”
Section: Mechanism Of Factors Affecting Ngpmentioning
confidence: 99%
“…In order to simulate land use change, many scholars have developed many models, such as the CLUE-S model [39,67,68], FLUS model [42,43,69] and PLUS model [70,71]. Recent studies have shown that most spatial models still have a high degree of uncertainty, which indicates no single model or method can fully describe the different processes of land use on all spatiotemporal scales [72][73][74]. In this study, a Markov model can describe the direction of land use change by considering the impact of relevant factors on land use demand, predict the future land demand of land use types, and allocate the predicted land demand to geospatial through FLUS model, so as to realize land use spatial prediction.…”
Section: Deficiencies and Future Directionmentioning
confidence: 99%